The Psychological Impact of Online Learning on Children During the COVID-19 Pandemic - Rafael Cruz; Juan Miguel (Program Studi DIII Rekam Medis dan Informasi Kesehatan, 2024)
The COVID-19 pandemic has accelerated the adoption of online learning, but its long-term effects on children's psychological well-being remain a concern. This paper investigates the impact of remote learning on students’ mental health, social interaction, and academic motivation. Based on surveys and case studies, the research highlights the challenges children face and suggests strategies to improve their online learning experiences.